2022
DOI: 10.1093/jpp/rgab083
|View full text |Cite
|
Sign up to set email alerts
|

Umbelliferone ameliorates oxidative stress and testicular injury, improves steroidogenesis and upregulates peroxisome proliferator-activated receptor gamma in type 2 diabetic rats

Abstract: Objectives Diabetes mellitus (DM) is a chronic disease associated with serious complications, including male infertility. Umbelliferone (UMB) is a coumarin with promising antioxidant, anti-inflammatory and other beneficial effects. This study investigated the ameliorative effect of UMB against testicular injury, oxidative stress and altered steroidogenesis in rats with type 2 DM. Methods Rats received a high fat diet for 4 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…In the diabetic testes, gene expression and LH/hCG-R content were reduced (Figures 3, 4, 7 and 8), which is consistent with previously obtained data on a decrease in the expression of LH/hCG-R in the testicular cells of diabetic animals with T2DM and T1DM [38,43,64,70]. A decrease in LH/hCG-R expression should result in a weakening of the steroidogenic response of Leydig cells to endogenous gonadotropins and, we believe, is one of the key causes of androgen deficiency in T2DM male rats.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the diabetic testes, gene expression and LH/hCG-R content were reduced (Figures 3, 4, 7 and 8), which is consistent with previously obtained data on a decrease in the expression of LH/hCG-R in the testicular cells of diabetic animals with T2DM and T1DM [38,43,64,70]. A decrease in LH/hCG-R expression should result in a weakening of the steroidogenic response of Leydig cells to endogenous gonadotropins and, we believe, is one of the key causes of androgen deficiency in T2DM male rats.…”
Section: Discussionsupporting
confidence: 91%
“…A histochemical analysis of the diabetic testes showed a decrease in the thickness of the seminiferous epithelium and the number of spermatogonia and pachytene spermatocytes (Figure 6; Table 6). Earlier, we and other authors have also demonstrated a decrease in the level of androgens, and an impaired spermatogenesis in rats with different models of T2DM [43,[63][64][65]. In the testes of diabetic rats, the structural disruption and atrophy of the seminiferous tubules, the reduced number of spermatogenic cells and their degeneration and disorganization and the disappearance of spermatids in the lumen of the seminiferous tubules were shown [43,63,65].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Several studies have shown that oxidative stress plays a role in the development of diabetic reproductive system damage and that antioxidants can help. According to the evidence, oxidative stress was the primary cause of the testicular malfunction, which resulted in male hypogonadism and infertility (Allam et al 2021). Hyperglycemia boosted mitochondrial glucose oxidation by releasing a large amount of superoxide and other free radicals into the cytoplasm, according to a study.…”
Section: Et Al (2017a)mentioning
confidence: 99%